Status of Vitamin D by measuring 25 - Hydroxyvitamin D level in Dhaka City (Bangladesh Journal of Medical Science, 2019)
Background and aims: Vitamin D deficiency is associated with skeletal as well as extraskeletal diseases. Aim of this study was to find out the status of Vitamin D level in a densely populated area like Dhaka.Method: This descriptive cross sectional study was conducted in Ibn Sina Medical College Hospital in Kallyanpur, Dhanmondi Ibn Sina Hospital and Ibn Dina Diagnostic Laboratory in Dhanmondi. Total 500 subjects who went for vitamin D assay were included in this study. Serum Vitamin D (25 - Hydroxyvitamin D) levels were measured by chemiluminescence immunoassay method. The respondents were divided in 4 age groups: ( 0-20) years, (21-40) years, (41-60) years and (61-rest) years. Data were presented by frequency distribution tables & graphs.Result: Out of the 500 respondents, 10.6% were in 0-20 age group, 30.8% were in 21-40 age group, 41.2% were in 41-60 age group and 17.4% were in 61-rest age group respectively. Mean age of total study subjects was 43.7 years. Male and female ratio was 33.2:66.8. Of the total 218(43.8%) participants had deficient level, 187(37.2%) had insufficient level, 90(18%) had sufficient level and only 5(1%) had toxic level of vitamin D.Conclusion: High prevalence of vitamin D deficiency was observed in 41 to 60 years age group people and female are more suffered than male. That’s why vitamin D status screening in this age group should be a routine test.Bangladesh Journal of Medical Science Vol.18(3) 2019 p.624-627